The predictive value of a targeted posterior fossa multimodal stroke protocol for the diagnosis of acute posterior ischemic stroke. Issue 1 (December 2016) - Sharon, Michal; Boyle, Karl; Yeung, Robert; zhang, Liying; Symons, Sean; Boulos, Mark; Aviv, Richard
Abstract Background There is limited but growing research regarding the accuracy of CTP in diagnosing acute posterior ischemia stroke. We sought to evaluate the diagnostic accuracy of an incremental multimodal CT protocol in acute posterior ischemic stroke. Methods Retrospective review of incremental NCCT, CTA-source images and CTP use in 82 consecutive patients with acute posterior ischemic stroke. Readers were blinded to infarct status on follow-up imaging (MRI or CT). Predictive effects of observed diagnostic accuracy and confidence score were quantified with the entropy r2 value. Sensitivity, specificity, and CI were calculated accounting for multiple reader assessments. Receiver Operating Characteristic analyses, including Area Under the Curve, were conducted for the three modalities. Inter-reader agreement was established with Intraclass Correlation Coefficient. Results Follow-up imaging confirmed infarct in 69/82 (84 %) patients. Multimodal protocol with CTP, outperforms CTA-source images and NCCT for correct acute posterior ischemia stroke diagnosis. The Area Under the Curve was 0.741 (95 % CI 0.708–0.773); 0.70 (95 % CI 0.663–0.731, P  = 0.03) and 0.62 (95 % CI 0.588–0.659, P  < 0.0001), respectively. Incrementally improved correlation between observed and actual diagnosis (r2  = 0.09, 0.26 and 0.32) and a higher rate of certainty (51.4, 69.3 and 81.7 %) was demonstrated for NCCT, CTA-source images and CTP respectively. Inter-reader agreement for the actual diagnosis was good and improved from 0.68 to 0.83 with incremental multimodal CT use. Conclusions CTP enhances confident and correct infarct diagnosis over NCCT and CTA-source images in acute posterior ischemia stroke.